Grazing and Supplementation of Dietary Yeast Probiotics Shape the Gut Microbiota and Improve the Immunity of Black Fattening Goats (Capra hircus) - Emu, Quzhe; Guan, Hao; Zhu, Jiangjiang; Zhang, Lin; Fan, Jinsheng; Ji, Yang; Lin, Yaqiu; Li, Chunmei; Dan, Xiaobo; Aguo, Yueda; Wei, Xiaolan; Zhang, Min; et al. (Frontiers in Microbiology, 2021)
This study aimed to investigate the effects of different feeding modes on the growth performance, gut microbiota, and immunity of Black Fattening Goat (Capra hircus). A total of 30 goats were grouped in three groups by their feeding modes (pasture grazing group, PG; barn feeding group, BF; barn feeding + probiotics, BF + P; n = 10) and the study was performed for 114 days. After a 2-week adaptation period, the first growth performance test was conducted, and the blood and fecal samplings (day 0) were collected on January 17, 2020, while the second and third test and samplings were conducted on days 53 and 100 of feeding. The species-composition of fecal microbiota was analyzed by 16S ribosomal RNA gene-sequencing using PacBio single molecule real time (SMRT) sequencing technology. Both the BF and BF + P groups had the highest (P < 0.05) body’s weight and length, and chest circumference at days 53 and 100, especially at day 100, the body’s weight of both the BF groups were more than 18 kg. The levels of immunoglobulin A (IgA) and immunoglobulin G (IgG) were found to be significantly higher (P < 0.05) in the PG and BF + P groups at day 100. The PG group exhibited the highest number of operational taxonomic unit (OTUs) and alpha diversity. Firmicutes, Bacteroidetes, and Verrucomicrobia were the predominant phyla in all the fecal samples. The relative abundance of Akkermansia muciniphila and Ruminococcus flavefaciens were found to be significantly higher (P < 0.05) in PG group and BF + P group at day 100, respectively, which might partially explain the significantly higher (P < 0.05) levels of IgA and IgG in these two groups. These findings suggested that BF supplemented with 5 g probiotics (Saccharomyces cerevisiae and mannan oligosaccharides) per day has the potential to enhance the growth and immunity of Black Fattening Goats.